1997
DOI: 10.1111/j.1440-172x.1997.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic programme for people with dementia

Abstract: A programme involving Tai Chi and structured reminiscence was trialed with nine people suffering from moderately advanced dementia. The analysis reported here aimed to examine stories the people told with a view to understanding the purpose of story telling in their lives. Themes derived from the narrative data had a strong evaluative quality, ranging from simple evocative expressions to more cognitive complex insights or treasures. The study indicated a major aim in story telling as being able to generate lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Significant improvement in mood was also reported in a RCT following short-term Tai Chi training [39]. Results from 3 NRS reported non-significant improvements in mood following 7 weeks to 1 year of Tai Chi [22,77,78] and one NRS reported a significant decrease in mood disturbance after an hour of Tai Chi practice [40]. Similarly, 3 OBS of 799 subjects reported that 0.5 to 14 years of Tai Chi practice significantly improved mood disturbance in healthy participants [62,63].…”
Section: Tai Chi and Moodmentioning
confidence: 92%
“…Significant improvement in mood was also reported in a RCT following short-term Tai Chi training [39]. Results from 3 NRS reported non-significant improvements in mood following 7 weeks to 1 year of Tai Chi [22,77,78] and one NRS reported a significant decrease in mood disturbance after an hour of Tai Chi practice [40]. Similarly, 3 OBS of 799 subjects reported that 0.5 to 14 years of Tai Chi practice significantly improved mood disturbance in healthy participants [62,63].…”
Section: Tai Chi and Moodmentioning
confidence: 92%
“…Nine elderly patients diagnosed with multiple-infarct dementia or Alzheimer disease participated twice weekly over 7 weeks in a before-and-after Tai Chi trial. 54 The authors concluded that "structured reminiscence with Tai Chi facilitated thinking that was focused and insightful, beyond the level normally manifested for this group of participants. "…”
Section: 50mentioning
confidence: 97%
“…One qualitative study of tai chi used focus groups of individuals with dementia (Gibb, Morris, & Gleisberg, 1997) and, therefore, was limited by recall. However, we believe that participant observation and interviews with caregivers may be more suitable methods for such investigation, are particularly suited to examine the nature of the participants' experience (Gibson, Timlin, Curran, & Wattis, 2004;Moore & Hollett, 2003), and have been used to examine implicit memory and social interactions in people with dementia.…”
Section: Introductionmentioning
confidence: 99%